The Influence of E-WOM, Service Quality, and Perceived Price on Biznet Home WIFI Subscription Decisions in Sidoarjo - Kevin Rafi Diaz Sandio; Ugy Soebiantoro; Egan Evanzha Yudha Amriel (PT Inovasi Pratama Internasional, 2023)
This study aims to determine the effect of E-WOM on the Decision to Subscribe to Biznet Home Wifi in Sidoarjo City, the effect of Service Quality on the Decision to Subscribe to Wifi Biznet Home in Sidoarjo City and the Effect of Perceived Price on the Decision to Subscribe to Wifi Biznet Home in Sidoarjo City. The population in this study is Biznet Home Customers in Sidoarjo City. The sample in this study used the Ghozali formula and found 112 respondents. The method used in this study uses the GForm form. The analysis technique in this study uses PLS (Partial Least Square). The results of this study indicate that the E-WOM indicator variable that has the highest percentage is I often consult with other consumers on social networking accounts regarding Biznet Home services. (X1.2), the variable Service Quality indicator that has the highest percentage is Biznet Home Officers who really understand the needs and difficulties of consumers (X2.4) while the Price Perception variable that has the highest percentage is the price offered by Biznet Home wifi which is quite competitive ( X3.4)